MILITARY INFLUENCE IN NIGERIAN POLITICS: ITS IMPACT ON AND IMPLICATIONS FOR THE DEVELOPMENT OF A DEMOCRATIC POLITICAL CULTURE - Ekemam, Hillary I (SOUTH EAST JOURNAL OF POLITICAL SCIENCE, 2021)
Contemporary Nigerian political scene since the incursion of the military in its body politic can be described as anything but democratic owing to the militaristic behaviors of its successive political leadership at various levels of government. This behavior has become worrisome in the light of its implications for Nigeria’s democratic development. This paper attempts an expose’ of the long military presence in Nigeria’s politics, its influence on the manifest behavioral patterns of its political leaders, and its implications for the development of a truly democratic political culture. Data for the study were sourced from secondary qualitative materials while analysis is descriptive-comparative and historical. Onuoha’s (2019) ‘Tout Theory of Politic is found appropriate for explication and comprehension of the trajectory of the paper. Our study reveals, among others, that the political culture of contemporary Nigeria has been influenced by not only the nature and character of the military, but by its long presence and/or meddlesomeness in the country’s democratic development. The paper is of the view that given this scenario the militaristic phenomenon will endure, hence sustaining the tout theoretical argument for the explanation of Nigeria’s contemporary political culture. It recommends, among others, a serious reorientation or re-socialization of the political class on democratic ethos, a constitutional amendment (provision) banning ex-military officers from running for an elective office and a downward review of perks and appurtenances of elective offices across the board.